A Brief Survey on Bio-inspired Algorithms for Autonomous Landing∗. Issue 1 (2016) - Maitra, Amritesh; Prasath, Sri Ram; Padhi, Radhakant
Abstract: The paper briefly introduces a few bio-inspired algorithms which can be applied to autonomous landing for Unmanned Aerial Vehicles (UAVs). A number of vision based data acquisition methodologies used for UAV navigation and guidance are described. Monocular camera based vision data can be used to extract plethora of information about the dynamics of a target plane in landing problems and also about the pose of the camera itself. Some recent developments in the areas of autonomous landing and perching based on vision data from monocular camera are introduced. Some possible relevant extensions are also provided.